Analisis Pembentukan Karakter Siswa dalam Pembelajaran IPA Melalui Pendekatan Al-Qur’an di SD Islamiyah Kota Ternate - Srinawati, Risna; Jusuf, Ridwan; Abdullah, Taufik (Universitas Khairun, 2023)
Character education is very fundamental in education, because morals and character are the main targets in education. Thus, the formation of student character must exist at the joint of general education and Islamic education, or integrate the two through an Al-Qur'an approach based on the Pancasila Education Profile. Science learning which contains natural events should not be separated from the Al-Qur'an, because in the Al-Qur'an all natural phenomena are explained, so that they are interrelated and mutually support each other in developing students' knowledge which leads to strengthening character. The existence of an Islamic-based elementary school should have added value in the character aspect by emphasizing the Al-Qur'an approach. Therefore, this research aims to analyze the formation of student character in science lessons through the Al-Qur'an approach at SD Islmaiyah 2, Ternate City and SD Islamiyah 5, Ternate City. This research method is descriptive qualitative using Miles and Huberman's interactive analysis model. The results of this research show that there is no integration of science lessons with the Al-Qur'an to encourage the development of student character education at Islamiya 2.5 Elementary School, Ternate City. This can be seen from the learning tools and learning process. Although the learning process has been touched upon a little, it is not yet structured due to the teacher's limited ability to integrate it. In the future, training is needed to develop learning tools using the Al-Qur'an approach to prepare the generation for a golden Indonesia in 2045.